Graphic Calculator As A Teaching And Learning Aid For Secondary School Students And Teachers. - Haili, Hailiza Kamarul; Lee, Boon Sim (2005)
This paper discussed the possibility and suggestion of the implementation of graphing calculator in teaching and learning Mathematics in the Malaysian's upper secondary school in order to meet the challenge of today's accelerated technology.